Assessment of risk factors for breast and ovarian cancer in UMS students - Ohnmar Myint; Than Myint; Aye Aye Wynn (2018)
Cancer is a major public health problem and the third leading cause of death in Malaysia . Breast and ovarian cancers are the first and fourth most common cancer among women in Peninsular Malaysia. Our aim is to assess the risk factors in healthy young adult female students from UMS and will act as an input for further prevention of breast and ovarian cancer. Total 278 Medical and Nursing students from Faculty of Medicine and Health Sciences were participate in this study. Assessing the hereditary risk factor, total 12.34% gives positive result for history of breast tumour in first degree relatives and for ovarian tumour total 1.8% gives positive results in first degree relatives. An overall mutation frequency of 2.3%, in woman who had at least one first-degree relative with breast cancer diagnosed at age <50 years ( Hartge et al. (1999) . The lifetime risk of breast cancer among female mutation carriers was 82% and lifetime risks of ovarian cancer were 54% for BRCA1 and 23% for BRCA2 mutation carriers. Risk reducing options are available to women with a strong family history of breast and ovarian cancer. These options include high-risk screening, chemoprevention, and prophylactic surgery. In our study, 63.7% is not meeting with WHO recommendation for Metabolic Equivalent Task (MET) and remaining 36.3% meets WHO recommendation. By using International Physical Activity Questionnaire (IPQA)Score protocol,only 2.6 % of Medical students showed Health Enhancing Physical Activity (HEPA) active,36.4 % showed minimally active and 60.9% showed inactive. Among nursing students only 5.5% showed HEPA active, 35.4% showed minimally active and 59.1% are inactive. Primary prevention through behavioural and life style modification is a cost-effective means of preventing the large burden cancer has on societies world-wide .